1975
DOI: 10.1002/ps.2780060507
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mode of testing on susceptibility to various insecticides of adults or larvae of Lucilia sericata, Chrysomya putoria and Musca domestica L

Abstract: Relative potency of eight compounds (four pairs of similar types) to adults and old larvae of three species of cyclorhaphous diptera was determined by injection, oral or topical application. The following points emerged from comparisons of equitoxic doses: (a) C. putoria was consistently more susceptible than L. sericata. M. domestica was more susceptible to organochlorines than either of the blowflies, but less susceptible to organophosphorus, carbamate or pyrethroid insecticides; (b) the most potent insectic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Contact treatments provided the highest LC5ss followed by oral treatments and then by injection of insecticide. Busvine & Iwuala (1975) also found a strong correlation between mode of application (oral versus contact) within the same stage (p<0.05; larvae r = 0.941, adult r = 0.837) but none between differenr stages (oral larval/adult r = -O.222 and contact larval/adult r = -0.174). This was consistent with Arnold & whitten's (1975) findings.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Contact treatments provided the highest LC5ss followed by oral treatments and then by injection of insecticide. Busvine & Iwuala (1975) also found a strong correlation between mode of application (oral versus contact) within the same stage (p<0.05; larvae r = 0.941, adult r = 0.837) but none between differenr stages (oral larval/adult r = -O.222 and contact larval/adult r = -0.174). This was consistent with Arnold & whitten's (1975) findings.…”
Section: Discussionmentioning
confidence: 83%
“…Howevern a mors detailed study of mode of insecticide application by Busvine & Iwuala (1975) reinforced Arnold & Whitten's (1975) findings of a lack of an adult/larval resistance relationship, although Busvine & Iwuala (1975) ignored insect weight. They showed that the mode of insecticide administration affected the relative potency of an insecticide in three Diptera, L. sericata and Chyrosomya putoria (which are phylogenetically related to L. cuprina (Erzinclioglu 1984)), and Musca d,omestica.…”
Section: Discussionmentioning
confidence: 98%